Prognostic impact of KRAS G12C mutation in patients with NSCLC: results from the European Thoracic Oncology Platform Lungscape project - Finn, Stephen P.; Addeo, Alfredo; Dafni, Urania; Thunnissen, Erik; Bubendorf, Lukas; Madsen, Line Bille; Biernat, Wojciech; Verbeken, Eric; Hernandez-Losa, Javier; Marchetti, Antonio; Cheney, Richard; Warth, Arne; et al. (Journal of thoracic oncology, 2021)
Introduction - KRAS mutations, the most frequent gain-of-function alterations in NSCLC, are currently emerging as potential predictive therapeutic targets. The role of KRAS-G12C (Kr_G12C) is of special interest after the recent discovery and preclinical analyses of two different Kr_G12C covalent inhibitors (AMG-510, MRTX849). - Methods - KRAS mutations were evaluated in formalin-fixed, paraffin-embedded tissue sections by a microfluidic-based multiplex polymerase chain reaction platform as a component of the previously published European Thoracic Oncology Platform Lungscape 003 Multiplex Mutation study, of clinically annotated, resected, stage I to III NSCLC. In this study, -Kr_G12C mutation prevalence and its association with clinicopathologic characteristics, molecular profiles, and postoperative patient outcome (overall survival, relapse-free survival, time-to-relapse) were explored. - Results - KRAS gene was tested in 2055 Lungscape cases (adenocarcinomas: 1014 [49%]) with I or II or III stage respective distribution of 53% or 24% or 22% and median follow-up of 57 months. KRAS mutation prevalence in the adenocarcinoma cohort was 38.0% (95% confidence interval (CI): 35.0% to 41.0%), with Kr_G12C mutation representing 17.0% (95% CI: 14.7% to 19.4%). In the "histologic-subtype" cohort, Kr_G12C prevalence was 10.5% (95% CI: 9.2% to 11.9%). When adjusting for clinicopathologic characteristics, a significant negative prognostic effect of Kr_G12C presence versus other KRAS mutations or nonexistence of KRAS mutation was identified in the adenocarcinoma cohort alone and in the "histologic-subtype" cohort. For overall survival in adenocarcinomas, hazard ratio (HR)G12C versus other KRAS is equal to 1.39 (95% CI: 1.03 to 1.89, p = 0.031) and HRG12C versus no KRAS is equal to 1.32 (95% CI: 1.03 to 1.69, p = 0.028) (both also significant in the "histologic-subtype" cohort). For time-to-relapse, HRG12C versus other KRAS is equal to 1.41 (95% CI: 1.03 to 1.92, p = 0.030). In addition, among all patients, for relapse-free survival, HRG12C versus no KRAS is equal to 1.27 (95% CI: 1.04 to 1.54, p = 0.017). - Conclusions - In this large, clinically annotated stage I to III NSCLC cohort, the specific Kr_G12C mutation is significantly associated with poorer prognosis (adjusting for clinicopathologic characteristics) among adenocarcinomas and in unselected NSCLCs.